Analisis Bibliometrik pada Database Dimensions dari Penelitian Moderasi Beragama di Era Digital - Riri Raudhotul Jannah; Busro Busro (Gunung Djati Conference Series, 2023)
Many researchers have researched using bibliometric analysis. Biblometric analysis is a study or data to be analyzed. And Bibliometrics is also a study of bibliographic analysis of scientific activities, especially what will be studied and discussed now regarding religious moderation in the digital era. This researcher aims to examine religious moderation in the digital era in the database dimension. This research method uses qualitative methods and bibliometric analysis on dimension databases and there are several stages carried out in the research, the first is determining keywords, the second is data search, the third is selecting articles with restrictions and publication trends in dimensions, the fourth data validation, and finally data analysis with visualization carried out by researchers on the database dimension. The results of this study show that the highest data research category is philosophy and religious studies with a total of 129 publications. And for the 2022 data search the highest is 96. And the trend of publications is the same in value and the name of the publication journal is fikrah with a total of 6. This research concluded that researchers must discuss religious moderation in the digital era which is examined using bibliometric analysis on the database dimension. This research is also very useful for the community, especially in this digital era. This research can and can be examined again to make it better.